Visual modeling of behavioural properties in the LVM for XML using XSemantic nets - Rajugan, R.; Chang, Elizabeth; Feng, L.; Dillon, Tharam S. (IEEE Computer Society Press, 2006)
Due to the increasing dependency on self-describing, schema-based, semi-structured data (e.g. XML), there exists a need to model, design and manipulate semi-structured data and the associated semantics at a higher level of abstraction than at the instance or document level. In this paper, we extend our research and propose to visually model (at the conceptual level) and transform dynamic properties of views in the Layered View Model (LVM) using the eXtensible Semantic (XSemantic) net notation. First, we present the modeling notation and then discuss the declarative transformation to map the dynamic XML view properties to XML query expressions, namely XQuery.